Antioxidant Activities, Phenolic Compounds and Organic Acids of Raw and Boiled Berries of Solanum Torvum Swartz From Eastern Côte d’Ivoire - Kouadio, Eugène Jean Parfait; Kouadio, Kouakou; Adingra, Kouassi Martial-Didier; Kouadio, Martin (Department of Technology of Agricultural product (THP) Jambi University, 2022)
Berries of solanum torvum, referred to as wild eggplant, are widely consumed in eastern Côte d'Ivoire in boiled form in sauces or soups. This study aimed to evaluate the antioxidant potential of these fruits through the estimation of antioxidant capacities of the extracts, identification and quantification of phenolic compounds and organic acids of raw berries and boiled berries to gauge the influence of this cooking. Results showed that boiling caused a considerable decrease in the antioxidant capacity of S. torvum berry extracts. By DPPH scavenging, the effective concentration (EC50) value of extract increased from 20.00 to 42.20 µg/mL, respectively for raw and boiled berries. Regarding EC50 values for antioxidant activities via FRAP, the values of 75.10 and 87.20 µg/mL were obtained, respectively for raw and boiled berries extract. In terms of phenolic compounds, the most predominant were catechin and gallic acid with respective contents of 1.06 and 0.86 mg/kg in the raw berries; 0.86 and 0.71 mg/kg in boiled berries, demonstrating the decrease in levels of these compounds by boiling. Organic acids showed the same decreasing trend during boiling. However, using cooking water when preparing soups or sauces could minimize these losses. In addition to this, one could consider other cooking methods such as steaming to better ensure nutrient retention